Foundations for Considering the Robustness within the CRC TRR 30 - Biermann, Dirk; Gausemeier, Jürgen; Hess, Stefan; K{\, Daniel; Petersen, Marcus; Wagner, T (Functionally Graded Materials in Industrial Mass Production | Volume 2)
The consideration of the robustness is indispensable to ensure a reliable and reproducible manufacturing of functionally graded components. In order to establish a common understanding as basis for the holistic robustness consideration within the Collaborative Transregional Research Centre 30 (CRC Transregio 30), a joint development of methods for analysing and optimising the robustness is necessary. The term "robustness", however, has been used differently in the various disciplines of the CRC Transregio 30. Thus, this contribution proposes a common definition of robustness for the whole research centre. In addition, a procedure model for considering the robustness with a collection of methods, that can be combined or adapted by the involved disciplines, is presented. The validation of the recommended procedure model has been conducted by a compression moulding process.

Concept for {\ "u} r an intelligent technology fr ü haufkl {\ "a} rung - Amshoff, Benjamin; Eckelt, Daniel (Scientific Society for Product Development WiGeP News)

Systematics for the development of business { \ "a} ftsmodellen in the product development - Gausemeier, J {\ "u} rgen; K ö ster, Oliver; R {\ "u} bbelke, René (Foresight and technology planning)

Synthesis and Multi-Objective Model-based Optimisation of Process Chains for Manufacturing Components with Functionally Graded Properties - Biermann, Dirk; Gausemeier, Jürgen; Hess, Stefan; Petersen, Marcus; Wagner, T (Functionally Graded Materials in Industrial Mass Production | Volume 2)
Functional gradation denotes the systematic and reproducible microstructure adjustment of a single material component for the customisation of the macroscopic properties (e.g. hardness or ductility). This customisation is tailored with respect to the later intended application of the component. The improved material utilisation enables light weight design and simplifies the recycling by using single material components. Hence, it provides a resource-conserving alternative for modern composite materials and offers an innovative approach for customisable smart products of the future. Manufacturing functionally graded components requires complex thermo-mechanically coupled process chains that increase the effort for the holistic design. To realise the full potential offered by functional gradation, the available planning and optimisation methods as well as the surrogate models developed during the first research period of the Collaborative Transregional Research Centre (CRC Transregio 30) are significantly enhanced. Furthermore, all the methods and surrogate models as well as the process knowledge obtained by laboratory experiments are consolidated in a comprehensive computer-aided framework to provide a continuous support for the engineer during the planning process. This contribution proposes the methodical foundations within the framework along the planning process: Component description, synthesis of suitable manufacturing process chains, and optimisation of the process chain parameters as well as the specification of the production system. The methods are validated based on an exemplary planning task within the CRC Transregio 30.

Planning Methods for Manufacturing Functionally Graded Components – Challenges and Solutions - Biermann, Dirk; Gausemeier, Jürgen; Hess, Stefan; Petersen, Marcus; Wagner, T (Functionally Graded Materials in Industrial Mass Production | Fundamentals)
Functional gradation denotes the systematic and reproducible adaption of the microstructure for the customisation of the macroscopic properties (e.g. hardness or strength) of a single material component. This customisation is tailored with respect to the intended application of the component. The improved material utilisation enables light weight design and improved recycling abilities. Hence, it provides a resource-conserving alternative for modern composite materials. To exploit the potential offered by functional gradation, the available planning and optimisation methods have to be significantly enhanced. Three-dimensional distributions of component properties have to be specified and predicted. Complex interdependencies between the manufacturing process steps and the properties of the component as well as between the process steps themselves have to be considered. In this contribution, new as well as enhancements of existing methods are presented along the planning process: Component description, synthesis of suitable manufacturing process chains, and optimisation of the process chain parameters. The resulting procedure model allows the specification of the desired property distribution, the subsequent identification of process chains capable of producing the component as well as the optimisation of each process parameter.

Fachdisziplinübergreifende Systemmodellierung mechatronischer Systeme mit SysML und CONSENS - Iwanek, Peter; Kaiser, Lydia; Dumitrescu, Roman; Nyßen, Alexander (Tag des Systems Engineerings)

Creation of process models for ü r the design of self-optimizing controls - Kessler, Jan Henning; Gausemeier, J {\ "u} rgen; Iwanek, Peter; K ö chling, Daniel; Kr {\ "u} ger, Martin; Tr {\ "a} chtler, Ansgar

Causality Between Terrorism and Economic Growth - Gries, Thomas; Meierrieks, DAniel (Journal of Peace Research)

Concept for a Task–Specific Reconfigurable Driving Simulator - Hassan, Bassem; Gausemeier, Jürgen (Proceedings of SIMUL 2013, the Fifth International Conference on Advances in System Simulation)

Scientific Automation rises the productivity of production facilites - Frank, Ursula; Anacker, Harald; Bielawny, Dirk